Efektivitas Penggunaan Ayunan dan Pemberian Pijat terhadap Kualitas Tidur Bayi di Puskesmas Rantepao - Nurhasanah Nurhasanah; Yusda Seman; Kristina Agus; Enggar Enggar (Jurnal Rumpun Ilmu Kesehatan, 2026)
Sleep is one form of adaptation of babies to their environment. Shortly after birth, babies sleep for 16-20 hours a day. At 2 months of age, babies begin to sleep more at night than during the day. At 3 months of age, newborns will spend about 15-17 hours sleeping, with 8 hours for naps and 9 hours for nighttime sleep. As the baby gets older, their sleep hours also decrease. At 3-6 months of age, the number of naps decreases, approximately 3 times. The total sleep time of babies aged 0-6 months ranges from 13-15 hours/day. At 6 months of age, their sleep patterns begin to appear similar to adults. This study aims to determine the effectiveness of the use of swings and massage on the quality of infant sleep at the Rantepao Community Health Center. The research method used a one-group pretest-posttest design. The population of all infants aged 0-6 months was 30 people. Statistical tests used a one-sample t test. The results showed that the sleep quality of babies aged 0-6 months who were rocked was predominantly in the good category, namely (53%) and those with poor sleep quality (27%). The sleep quality of babies aged 0-6 months after baby massage was predominantly in the good category (54%) and those with poor sleep quality (13%). Swinging and baby massage are effective in improving the quality of baby sleep with a p value of 0.000 <0.05. So it is necessary to develop promotions and education to the community, especially parents, to improve the quality of baby sleep.